Analisis Kelayakan Rencana Investasi Mesin Produksi Guna Memenuhi Permintaan - Heri Mujayin Kholik (Jurnal Teknik Industri, 2007)
Eka Surya Makmur is a company that produce plastic bag. For couple years before, this company can't fill the customers demand because the machine capacity. Because of that, the labor working overtime, but still not optimal and effected to financial aspect significantly. That's way, need accurate analysis to minimize the failed effect and increase company income. To solve the problem, its suggest to use Prediction Method to predicted the future quantitatively based on current data. NPV (Net Present Value) is different value between current investment and reseipt net cash in future. IRR (Internal Rate of Return) is current interest level same with current cash flow or cash receipt in first investment. PI (Profitability Index) is ratio between present value proceed with present value outplay. PP (Payback Period) is payback parameter investment. The research result is that machine investment properly to conduct to avoid overtime job, and as financial aspect can increase net income. From financial prediction knew that demand increase 10% every year; NPV = Rp. 94.803.643.788; IRR = 40%; PI = 54,41 %; PP = 0,06 year (21,9 days).